Listen to what the body says : a new model of unnatural narratology - Kang Mengni (Nanyang Technological University, 2020)
In an effort to make sense of unnatural narratives, there has been an ongoing debate between the textual and the cognitive approaches. In practice, it seems that the adoption of either approach inevitably cancels the other out, and a cooperation between the two is difficult to achieve. While the unnatural is essentially a textual phenomenon, it is after all human creation and supposedly carries communicative ends. Therefore, it is the position of this thesis that both the ontological status and the cognitive implication of unnaturalness should be taken into account. But how to conceptualize a model by which the two approaches mutually complement rather than neutralize? I suggest to add a phenomenological dimension to the current discussion, and relate readers’ affective reactions to the follow-up interpretation: I argue that the difference in the reader’s phenomenological experience of unnatural narratives hints at different reading strategies. My model highlights the interpretation of unnatural works as a constant negotiation between the text and the reader’s lived experience, which necessitates an ongoing dialogue between the two sense- making methods. With the reader’s experiencing body under consideration, my model aims to offer a more contextualized and holistic interpretation of unnatural narratives. In this thesis, I also put my model of unnatural narratology into practice, and demonstrate how it performs in three phenomenologically-divergent unnatural narratives—The Infernal Desire Machines of Doctor Hoffman, If on a Winter’s Night a Traveller, and Timbuktu. My analysis shows that unnatural works may provoke different affective responses in readers; moreover, one’s affective experience of a single unnatural text is never unified. Therefore, in the light of the mind- body continuum, the production of meaning should do justice to the phenomenological fact. This also means that the interpretive move should be localized: I examine the interaction between the iv unnatural and other contextual factors, as well as the rivalry between the invented nature and the emotional baggage of the unnatural. In this way, the flexibility and contextuality of sense-making activities is underlined.